Evaluation of Ehretia Laevis Roxb. (Khandu Chakka/Ajan Vruksha) in the Wound Healing Adjudged by Histological Examination of the Tissue - Rushikesh Thakre; Arvinda Bhake; Pradip Tekade; Ketaki Harne; Preeti Sujit Borkar (Institute of Medico-legal Publications Pvt Ltd, 2021)
Many herbal plants are mentioned in Ayurveda for wound healing. Folklore medicine for various ailmentsincluding wound healing is being practiced in India. Ehretia Laevis Roxb. contains many such chemicalcompounds useful for promotion of healing & repair. Tissue renewal goes hand in hand with inflammationinfluenced by multiple processes. Ehretia Laevis Roxb. called Khandu Chakka & Ajan Vruksha andtraditionally being used for wound healing, body pain & minor fractures in the form of local application byfolklore in the state of Maharashtra India. Objectives of the present study is to know the effect of EhretiaLaevis Roxb. in the wound healing on the histological parameters in animal model. Phenytoin ointmentas a control was used. The present study has found put that leaf extract paste of Ehretia Laevis Roxb.has enhanced the process of wound healing ascertained on histological parameters as compared to topicalphenytoin application. Ehretia Laevis Roxb. paste is found to be immensely useful at wound healing ascompared to Phenytoin. Ehretia Laevis Roxb. is concluded to promote the healing significantly as observedby feature of granulation, collagenisation & re epithelisation of the wounds suggesting early healing byprimary intension